2020
DOI: 10.1590/1983-1447.2020.20190370
|View full text |Cite
|
Sign up to set email alerts
|

Review of nursing diagnosis validation studies: caregiver role strain

Abstract: Objective: To analyze the nursing diagnosis NANDA-I - Caregiver Role Strain validation studies. Methods: Integrative literature review. Research of studies carried out between 2000 and 2018 with the descriptors: caregivers, nursing diagnosis and validation study in the following databases: Web of Science, EBESCOhost, Scielo Brasil and Portugal, LILACS, RCAAP, CAPES, NANDA-I website, and in the bibliographic references of the articles. Articles in Portuguese, English or Spanish were included. Results: The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The exercise of clinical reasoning aids diagnostic accuracy and enables adequate targeting of nursing interventions to achieve better health goals (Freitas & Conceição, 2018). The synthesis of knowledge, proposed in this protocol will facilitate the nurse's clinical judgment (Lourenço et al, 2020), and the decision-making regarding the instrument or scale for insomnia.…”
Section: Resultsmentioning
confidence: 99%
“…The exercise of clinical reasoning aids diagnostic accuracy and enables adequate targeting of nursing interventions to achieve better health goals (Freitas & Conceição, 2018). The synthesis of knowledge, proposed in this protocol will facilitate the nurse's clinical judgment (Lourenço et al, 2020), and the decision-making regarding the instrument or scale for insomnia.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studies of diagnostic accuracy are essential to identify a set of DCs and to evaluate the relationship of these indicators with diagnostic hypotheses in the most diverse health contexts. In this sense, the knowledge of clinical indicators that have better predictability for a given nursing diagnosis favors nurses to assertively targeting conducts and decision making in care practice, which implies achieving good nursing outcomes (Lourenço et al., 2020; Silva et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…"Inattentive to diseases symptoms," "inattentive to diseases signs," and "exhibits disease sequelae" were characteristics with specificity close to or equal to 1, suggesting that these characteristics behave as confirmatory indicators of the presence of Ineffective health self-management. given nursing diagnosis favors nurses to assertively targeting conducts and decision making in care practice, which implies achieving good nursing outcomes (Lourenço et al, 2020;.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has undergone several changes aimed at improving it, it still maintains a high number of defining characteristics and related factors, which can hinder its use. In a previous integrative review, it was found that, although seven validation studies (content/clinical) of the diagnosis had already been carried out, none of them was conducted among caregivers of patients in need of palliative care 12 .…”
Section: Introductionmentioning
confidence: 99%